2011
DOI: 10.1074/mcp.m111.011213
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein Rrm4 is Essential for Efficient Secretion of Endochitinase Cts1

Abstract: Long-distance transport of mRNAs is crucial in determining spatio-temporal gene expression in eukaryotes. The RNA-binding protein Rrm4 constitutes a key component of microtubule-dependent mRNA transport in filaments of Ustilago maydis. Although a number of potential target mRNAs could be identified, cellular processes that depend on Rrm4-mediated transport remain largely unknown. Here, we used differential proteomics to show that ribosomal, mitochondrial, and cell wall-remodeling proteins, including the bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 88 publications
6
77
0
Order By: Relevance
“…mRNA molecules are attached to endosomes and thus hitchhike these organelles (12). Most interestingly, the transport mechanism appears to be required for the proper localization of several mitochondrial proteins (13). This suggests transient association of kinesin-3 with mitochondria for delivery of mRNA encoding mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…mRNA molecules are attached to endosomes and thus hitchhike these organelles (12). Most interestingly, the transport mechanism appears to be required for the proper localization of several mitochondrial proteins (13). This suggests transient association of kinesin-3 with mitochondria for delivery of mRNA encoding mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data obtained from U. maydis may explain the somewhat contradictory results. It was shown recently that Kin3 of U. maydis is involved in mRNA transport (11,13). mRNA molecules are attached to endosomes and thus hitchhike these organelles (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the RNA-binding domain is functionally important, and Rrm4 does not hitchhike on transported mRNAs, but is an integral part of the transport unit (König et al, 2009). According to current views, microtubule-dependent transport of mRNPs is important for determination of the subcellular localisation of targets such as the small G protein Rho3 at retraction septa, as well as crucial for efficient secretion of the endochitinase Cts1 (König et al, 2009;Zarnack and Feldbrügge, 2010;Koepke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In such rapidly elongating filaments, long-distance transport, including endosomal RNA transport, becomes important (13,17). Previous studies on the RNA-binding protein Rrm4 identified the chitinase Cts1 as a potential target of active mRNA transport (18). Interestingly, Cts1 is unconventionally secreted (19).…”
mentioning
confidence: 99%